Preparation method of high-temperature-resistant alumina fiber rope
Through the mixing and optimization process of high-purity alumina powder and additives, the problems of high energy consumption and insufficient coating adhesion in traditional alumina fiber production are solved, and the high mechanical properties and high temperature stability of the fiber are achieved, reducing environmental risks .
Patent Information
- Application Number
- CN202411506096.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-14
AI Technical Summary
The traditional alumina fiber production process has problems such as high energy consumption, low production efficiency, environmental safety hazards and insufficient coating adhesion, which affects the mechanical properties and durability of the fiber.
Alumina fibers are prepared by mixing high-purity alumina powder with a preferred additive by heating and melting and brushing, twisting and annealing, and finally antioxidant coating treatment is carried out to improve the mechanical properties of the fibers and coating adhesion.
It significantly improves the mechanical properties and high temperature stability of alumina fibers, reduces environmental risks, and extends the service life of the material in high temperature environments.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of alumina fiber preparation, and relates to a method for preparing a high-temperature resistant alumina fiber rope. Background Art
[0002] The traditional alumina fiber production process is carried out under high temperature conditions. Although it can obtain excellent high temperature resistance, it has many shortcomings in terms of energy consumption, production efficiency and environmental safety. In addition, the existing production process also has the following main problems: the commercially available alumina powder has low purity, the cleaning steps are not thorough enough, and the surface impurities and oil stains cannot be effectively removed, resulting in insufficient coating adhesion. The twisting process lacks precise control of the twisting speed and twisting ratio, resulting in loose fiber bonding, affecting the mechanical properties and durability of the fiber rope. The coating has insufficient adhesion and durability, which affects the service life of the material in a high temperature environment. Some traditional processes use chemical additives, which will cause certain safety hazards to the environment and operators. The present invention clarifies the selection of additives and their ratios, optimizes the use of materials, and reduces potential environmental risks. Summary of the invention
[0003] Aiming at the problems existing in the production of traditional alumina fiber ropes, the present invention proposes a novel method for preparing high-temperature resistant alumina fiber ropes.
[0004] In order to achieve the above object, the present invention is implemented by adopting the following technical solutions: A method for preparing a high temperature resistant alumina fiber rope comprises the following steps: a. Mix alumina powder having a purity of not less than 99.9% with an additive to obtain a mixture; b. heating the mixture to 1600-2000°C to melt the mixture, and preparing alumina fibers by a wire drawing process; c. Weaving alumina fibers into fiber ropes through a twisting process; d. The fiber rope is annealed at 1000-1100°C.
[0005] The preparation process of high-purity alumina powder in step a is as follows: dissolving an aluminum salt (such as aluminum sulfate, aluminum chloride) in water to form an aluminum ion solution, then adding sodium hydroxide or ammonia water to adjust the solution pH to 7-9, so that the aluminum ions are precipitated as aluminum hydroxide (Al(OH)3), then removing impurities in the precipitate by centrifugation or filtration, and washing it with deionized water for multiple times, and then drying the precipitate at 60-100°C to obtain aluminum hydroxide powder, and finally calcining the dried aluminum hydroxide powder at 1200-1600°C for 2 to 6 hours to obtain aluminum oxide powder; using a high-speed airflow to accelerate aluminum oxide particles, and crushing them by collision and shear force, so that the particle size of the aluminum oxide powder is 5-10μm.
[0006] The additive is any one of calcium aluminate, magnesium silicate or aluminosilicate, wherein if the additive is calcium aluminate, the mass ratio of alumina powder to calcium aluminate is between 70:30 and 90:10; if the additive is magnesium silicate, the mass ratio of alumina powder to magnesium silicate is between 60:40 and 80:20; if the additive is aluminosilicate, the mass ratio of alumina powder to aluminosilicate is between 70:30 and 85:15.
[0007] Preferably, in step b, the diameter of the alumina fiber is between 5-10 μm.
[0008] Preferably, in step c, the alumina fibers are washed with deionized water or ethanol solution, and then dried at a temperature of 60°C-80°C to avoid fiber damage. Then, during the twisting process, the washed and dried alumina fibers are placed in a twisting machine at a predetermined ratio (for example, 3 fibers per bundle), and twisted using a double twisting process to form a fiber rope; wherein, during the twisting process, the twisting speed is set to 200-300 rpm, and the twisting ratio is set to 20-40% to ensure close bonding between the fibers; during twisting, the twist of the twisting machine should be controlled at 80-100 twists / m to reduce the internal stress of the fibers and improve the twisting effect.
[0009] Preferably, the fiber rope needs to be treated with an anti-oxidation coating after annealing, and the coating is a SiC or TiO2 coating. The specific preparation process is: use deionized water or ethanol to thoroughly clean the fiber rope to remove possible dust, grease and other contaminants, and then dry it naturally or dry it at 60°C after cleaning to ensure that there is no moisture on the surface; in order to improve the adhesion of the coating, use 10% to 20% hydrofluoric acid to slightly etch the fiber surface, the etching time is between 1 and 10 minutes, and then the fiber rope is completely immersed in a 5-15% SiC or TiO2 coating solution for 5-10 minutes. After dipping, slowly take it out and drip off the excess coating solution. After coating, place the fiber rope in a well-ventilated environment, and the drying time is generally 2-4 hours. In order to improve the durability of the coating, it can be thermally cured in an oven at 60°C for 1-2 hours to ensure that the coating is completely cured. The thickness of the coating is preferably 0.5-5μm.
[0010] Compared with the prior art, the advantages and positive effects of the present invention are: The present invention adopts homemade alumina particles for production, which can effectively improve the purity of alumina powder and control the particle size of the powder. And through the subsequent calcination process, the crystal phase structure of alumina is optimized, and the thermal stability and chemical resistance of the fiber product are improved. The type of additives and the dosage ratio of alumina have a great influence on the mechanical strength of alumina fiber products. The present invention significantly improves the mechanical properties of the fiber, especially the mechanical properties at high temperature, by adjusting the ratio and optimizing the process. DETAILED DESCRIPTION
[0011] In order to more clearly understand the above-mentioned purpose, features and advantages of the present invention, the present invention is further described below in conjunction with specific embodiments. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.
[0012] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways than those described herein. Therefore, the present invention is not limited to the specific embodiments of the following disclosure.
[0013] Example 1 Aluminum chloride is dissolved in deionized water to form an aluminum ion solution with a solution concentration of 50g / L. Ammonia water with a mass fraction of 60% is added to the solution and the pH of the solution is adjusted to 8.0, and the aluminum ions are precipitated as aluminum hydroxide (Al(OH)3). Centrifuge at 8000rpm for 5min to obtain an aluminum hydroxide precipitate solid, and wash the aluminum hydroxide precipitate 3 times with deionized water. Dry the aluminum hydroxide precipitate at 60°C for 30min to obtain aluminum hydroxide powder. Calcine the aluminum hydroxide powder at 1400°C for 4 hours to obtain aluminum oxide powder. Use a high-speed air flow to accelerate the aluminum oxide particles to 200m / s, and crush them by collision and shear force to obtain aluminum oxide powder with an average particle size of 5 microns. After testing, the aluminum oxide powder obtained in this embodiment has a purity of 99.9%, a crystallinity of 95%, and a specific surface area of 185m 2 / g, the peak position of XRD analysis is located at 1650cm -1, mainly α-Al2O3. Alumina powder is mixed evenly with an appropriate amount of calcium aluminate additive (calcium aluminate: alumina powder mass ratio 80:20). The mixture is heated to 1700℃ and maintained at this temperature for 30 minutes to melt the mixture. The melt is drawn into alumina fibers with a diameter of 8 microns by a wire drawing process. The obtained alumina fibers are washed with deionized water to remove surface impurities. After washing, a second washing is performed with a 50% mass fraction ethanol solution to ensure that there is no oil or other contaminants. Drying treatment is performed at 60℃ for 1h to avoid fiber damage caused by excessive heating. Three fibers are placed in each group in a twisting machine, and the twisting speed is set to 250 rpm and the twisting ratio is 30%. During the twisting process, the twist of the twisting machine is controlled to 80 twists / m to ensure that the fibers are tightly combined. The woven fiber rope is placed in a high-temperature furnace and annealed at 1000℃ for 4 hours. This annealing process can ensure that the mechanical properties of the fiber rope are enhanced without melting or excessive oxidation. Soak the fiber rope in deionized water for thorough cleaning to remove any dust or oil. Allow the cleaned fiber rope to dry naturally for 5 hours. Then use a 10% hydrofluoric acid solution for etching for 5 minutes to improve the adhesion of the coating. Immerse the etched fiber rope in a 10% SiC coating solution for 7 minutes. After soaking, remove it, drip off the excess solution, and place the fiber rope in a ventilated environment to dry naturally for 4 hours. To improve the durability of the coating, heat cure the dried fiber rope in a 60°C oven for 1 hour to ensure that the SiC coating is fully cured.
[0014] Example 2 The present embodiment is consistent with the embodiment 1 except for the special description. Aluminum sulfate is dissolved in deionized water to form an aluminum ion solution with a solution concentration of 80 g / L. Ammonia water is used to adjust the solution pH to 7.5, so that the aluminum ions are precipitated as aluminum hydroxide. Centrifugation is used to remove impurities, and the aluminum hydroxide precipitate is washed 4 times with deionized water. The aluminum hydroxide precipitate is dried at 80°C for 1 hour to obtain aluminum hydroxide powder. The aluminum hydroxide powder is calcined at 1600°C for 5 hours to obtain aluminum oxide powder. Alumina powder with an average particle size of 7 microns is obtained by air flow pulverization. The aluminum oxide powder is mixed evenly with a magnesium silicate additive (magnesium silicate: aluminum oxide powder mass ratio 75:25). The mixture is heated to 1850°C and kept for 30 minutes to melt it. The melt is drawn into an aluminum oxide fiber with a diameter of 8 microns by a wire drawing process. The aluminum oxide fiber is washed with deionized water to remove surface impurities and oil stains. The washed fiber is dried at 80°C for 1 hour to avoid fiber damage. Put three fibers into a twisting machine, set the twisting speed to 220 rpm, and the twist ratio to 35%. During the twisting process, keep the twist of the twisting machine at 95 twists / m to ensure close bonding between the fibers. Put the woven fiber rope into a high-temperature furnace and anneal at 1100°C for 3 hours. Soak the fiber rope in deionized water to clean it to remove possible dust and oil. After cleaning, dry the fiber rope at 60°C to ensure that there is no moisture on the surface. Use 15% hydrofluoric acid solution for etching, and the treatment time is 8 minutes. Immerse the fiber rope in a TiO2 coating solution with a mass fraction of 12% and keep the immersion time for 6 minutes. After taking it out, dry the fiber rope in a ventilated environment for 4 hours. Finally, the fiber rope is thermally cured in a 60°C oven for 1 hour to ensure that the TiO2 coating is completely cured.
[0015] Example 3 The parts not specially explained in this embodiment are consistent with those in Example 1. Aluminum silicate is mixed with alumina powder, and the mass ratio of alumina powder:aluminum silicate is 80:20. Heat the mixture to 1900°C to melt it, and make alumina fibers by a wire drawing process. The alumina fibers are drawn in the same way as in Example 1 to obtain alumina fibers with a diameter of 8 microns. According to the method in Example 1, the fibers are cleaned and dried and then twisted to ensure that the fibers are tightly combined, and the twisting ratio is set to 25%. The fiber rope is annealed according to the method in Example 1, and the temperature is set to 1100°C. The coating is performed according to the method in Example 2, and immersion is performed using SiC with a mass fraction of 10%.
[0016] The fiber test results obtained in Examples 1-3 are shown in Table 1 below.
[0017] The heat resistance temperature test process is that the material is placed in a muffle furnace and treated at the test temperature for more than 30 minutes. There is no obvious change on the surface of the material and no obvious change in mechanical strength. The test temperature is increased by 50°C each time until there is a significant change in the appearance or mechanical strength of the material.
[0018] Table 1 Fiber test data obtained in each embodiment From the test results in Table 1 above, it can be seen that the fiber prepared by the present invention has excellent mechanical properties and high temperature resistance, and the tensile strength of the fiber does not decrease significantly at a high temperature of 1000°C.
[0019] Comparative Example 1 In this comparative example, the ratio of alumina powder to calcium aluminate is adjusted to 10:1 by mass, and the other conditions remain unchanged. After testing, the final tensile strength of the alumina fiber obtained at room temperature is 169.1MPa. It can be seen that when the alumina powder is excessive, the brittleness of the material will increase and the toughness will decrease. The ratio of alumina powder to calcium aluminate is adjusted to 2:1 by mass, and the tensile strength of the alumina fiber product obtained at room temperature is 214.8MPa. It can be seen that when the additive is excessive, the strength of the product will also decrease. After the wear resistance test, when the additive is excessive, the wear resistance of the fiber is also significantly reduced.
[0020] Comparative Example 2 The alumina in Example 1 was replaced with commercially available alumina powder (5 microns, Sumitomo, Japan, purity 95%), and the rest of the preparation process and material dosage were consistent with Example 1. After testing, the tensile strength of the fiber obtained in this comparative example was 298.4 MPa at room temperature, and after being treated at 1000°C for 30 minutes, the coating on the surface of the material showed obvious bulging and falling phenomena.
[0021] The above description is only a preferred embodiment of the present invention and does not limit the present invention in other forms. Any technician familiar with the profession may use the technical content disclosed above to change or modify it into an equivalent embodiment with equivalent changes and apply it to other fields. However, any simple modification, equivalent change and modification made to the above embodiment based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a high temperature resistant alumina fiber rope, characterized in that: Here are the steps: a. Mix alumina powder having a purity of not less than 99.9% with an additive to obtain a mixture; b. heating the mixture to 1600-2000°C to melt the mixture, and preparing alumina fibers by a wire drawing process; c. After washing and drying the alumina fibers, the fibers are twisted to obtain a fiber rope; d. The fiber rope is annealed at 1000-1100°C.
2. The method for preparing the high temperature resistant alumina fiber rope according to claim 1, characterized in that: The alumina powder in step a is prepared by the following process: dissolving a soluble aluminum salt in water, then adding alkali to adjust the pH to 7-9 to generate an aluminum ion precipitate, centrifuging or filtering the precipitate and washing it several times, then drying it at 60-100°C to obtain a solid; calcining it at 1200-1600°C for 2-6h, and crushing it under high-speed airflow to obtain an alumina powder with a particle size of 0.5-10μm.
3. The method for preparing the high temperature resistant alumina fiber rope according to claim 1, characterized in that: The auxiliary agent in step a is any one of calcium aluminate, magnesium silicate or aluminosilicate, the mass ratio of alumina powder to calcium aluminate is 70:30-90:10; the mass ratio of alumina powder to magnesium silicate is 60:40-80:20, and the mass ratio of alumina powder to aluminosilicate is 70:30-85:
15.
4. The method for preparing the high temperature resistant alumina fiber rope according to claim 1, characterized in that: In step b, the diameter of the alumina fiber is 5-10 μm.
5. The method for preparing the high temperature resistant alumina fiber rope according to claim 1, characterized in that: In step c, deionized water or ethanol solution is used for cleaning, and the drying temperature is 60-80° C.; the twisting speed is 200-300 rpm, the twisting ratio is 20-40%, and the twist of the twisting machine is 80-100 twists / m.
6. The method for preparing the high temperature resistant alumina fiber rope according to claim 1, characterized in that: After the fiber rope is annealed, it is coated with an anti-oxidation coating. The process is as follows: the fiber rope is cleaned and dried, then etched with 10-20% hydrofluoric acid by mass for 1-10 minutes, then immersed in 5-15% SiC or TiO2 coating liquid by mass for 5-10 minutes, and then slowly taken out after the dipping is completed, naturally dried for 2-4 hours, and then dried at 60°C for 1-2 hours.
7. The method for preparing the high temperature resistant alumina fiber rope according to claim 6, characterized in that: The thickness of the coating is 0.5-5 μm.
Citation Information
Patent Citations
Ultrahigh aluminum glass product produced by adopting process method of new transverse flame tank furnace production system
CN110510868A
Preparation method of high-purity aluminum oxide powder
CN118479517A
High-purity alumina fiber and inorganic fiber product
JP1999043826A
Heat-resistant material
JP2003105682A
Inviscid melt spinning of mullite fibers
US6312626B1